2011
DOI: 10.1099/jmm.0.024166-0
|View full text |Cite
|
Sign up to set email alerts
|

Screening for novel quorum-sensing inhibitors to interfere with the formation of Pseudomonas aeruginosa biofilm

Abstract: The objective of this study was to screen for novel quorum-sensing inhibitors (QSIs) from traditional Chinese medicines (TCMs) that inhibit bacterial biofilm formation. Six of 46 active components found in TCMs were identified as putative QSIs based on molecular docking studies. Of these, three compounds inhibited biofilm formation by Pseudomonas aeruginosa and Stenotrophomonas maltophilia at a concentration of 200 mM. A fourth compound (emodin) significantly inhibited biofilm formation at 20 mM and induced pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 58 publications
4
79
1
1
Order By: Relevance
“…Previously published data indicated notable activity of shikonin derivatives against gram positive bacteria (and generally low activity against gram negative bacteria), with the fact of remarkable differences of antibacterial potency due to different approaches of measuring MIC values (Papageorgiou et al, 1999[23]; Andujar et al, 2013[3]). On the other hand, some results showed good antibacterial activity against some gram negative species (Brigham et al, 1999[4]; Ding et al, 2011[9]). Our results indicated that isolated naphthoquinone derivatives at the same time showed a good activity towards both gram positive and gram negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published data indicated notable activity of shikonin derivatives against gram positive bacteria (and generally low activity against gram negative bacteria), with the fact of remarkable differences of antibacterial potency due to different approaches of measuring MIC values (Papageorgiou et al, 1999[23]; Andujar et al, 2013[3]). On the other hand, some results showed good antibacterial activity against some gram negative species (Brigham et al, 1999[4]; Ding et al, 2011[9]). Our results indicated that isolated naphthoquinone derivatives at the same time showed a good activity towards both gram positive and gram negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Since many plant bacterial pathogens use type III secretion systems to cause disease and sense flavonoids 30 , it is possible that some of these compounds may have evolved as a consequence host-pathogen interactions. Moreover, flavonoids have also been reported to target other anti-infective properties such as expression of virulence genes 31,32 , toxin activity 33-35 , quorum sensing 36-39 and biofilm formation 40,41 in bacterial pathogens as well as attenuate destructive host inflammation 42-44 . Given the broad pharmacological activities of flavonoids, these plant metabolites may affect microbial virulence mechanisms, including type III protein secretion substrates shown here, in addition to host pathways for their anti-infective properties in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…[5] Indeed, since the extracellular polymeric matrices of biofilms protect bacterial cells, most antibiotic treatments are ineffective. [6] Several strategies, such as modified surfaces [7] , silver particle doped materials [89] and anti-quorum sensing drugs [1011] have been suggested over the last decades to either prevent or exterminate biofilms. Yet, the problem of biofilm formation and concomitant catheter induced infections persists, suggesting that other novel and more effective strategies are needed.…”
Section: Introductionmentioning
confidence: 99%